Curcumin inhibits the expression of ornithine decarboxylase and adenosine deaminase genes in MCF-7 human breast cancer cells - Abbaspour, Hossein; Safipour Afshar, Akbar (Archives of Biological Sciences, 2018)
Paper description: Curcumin, a multi-target compound, expresses anti-tumor activity in different pathways, including ornithine decarboxylase 1 (ODC1) and adenosine deaminase (ADA) inhibition. The roles of these enzymes have been investigated in curcumin-related studies at the level of enzyme activities; inconclusive experiments have been conducted at the protein expression level. In the human breast cancer cell line MCF7, Western blotting and real time PCR revealed downregulation of ODC1 and ADA by curcumin at the transcription level. We concluded that this was the result of reduced gene expression. Curcumin could suppress the proliferation of breast cancer cells through downregulation of ODC1 and ADA genes. Abstract: Curcumin is the active ingredient of Curcuma longa, which inhibits the development of malignant cells. Prevention and treatment of cancer by natural compounds, especially curcumin, and understanding the mechanism of action, is an area of interest in cancer research. In this study, we evaluated the effects of curcumin on cell proliferation, ornithine decarboxylase 1 (ODC1) and adenosine deaminase (ADA) gene expression in human breast cancer cell line (MCF-7) as compared to the non-cancer line (MCF-10A). Both cell lines were subjected to increasing doses of curcumin, ranging from 0 to 30 μg/mL. Cell viability was quantified by the MTT assay. In vitro clonogenic survival assay was performed on MCF-7 cells. Expression of ADA and ODC1 were analyzed by Western blotting and qRT-PCR. Curcumin inhibited the growth of malignant cells in a time- and dose-dependent manner. The calculated IC50 value for MCF-7 cells in 48 h was 12 μg/mL. Forty-five to 70% decreases in colony formation were observed in MCF-7 cells treated with 30-60 μg/mL curcumin, respectively. Our data revealed a dose-dependent downregulation of ODC1 and ADA expression and respective enzyme activities by curcumin, which correlated with decreased proliferation in the MCF-7 breast cancer cell line. These data suggest that curcumin represses the proliferation of breast cancer cells through downregulation of ODC1 and ADA gene expression, which might be another mechanism of curcumin-mediated tumor growth inhibition. https://doi.org/10.2298/ABS180209025A Received: February 9, 2018; Revised: May 21, 2018; Accepted: May 29, 2018; Published online: May 31, 2018 How to cite this article: Abbaspour Hossein, Safipour Afshar A. Curcumin inhibits the expression of ornithine decarboxylase and adenosine deaminase genes in MCF-7 human breast cancer cells. Arch Biol Sci. 2018;70(4):639-45.